2012
DOI: 10.4236/opj.2012.23023
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Microstructural, Structural, Optical and Electro-Optical Properties of La Doped Pmn-Pt Transparent Ceramics

Abstract: Transparent relaxor ferroelectric ceramics of the system lanthanum modified lead magnesium niobate have been investigated for a variety of electro-optic properties could make these materials alternatives to (Pb,La)(Zr,Ti)O<sub>3</sub>. However, a study that relates the properties in function stoichiometric formula, it has not been analyzed heretofore. Therefore, in this work the effect of A-site substitution of La<sup>+3</sup> in the characterization microstructural, structural, optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The density exhibits an increasing tendency as the BTO concentration is greater, also, it can be seen higher densities for the ceramic obtained from calcined powders to 900 °C. The densities are greater than 98%, which is especially suitable for electronic industry application, however, these powders presented a major quantity of secondary phases [16].…”
Section: Resultsmentioning
confidence: 99%
“…The density exhibits an increasing tendency as the BTO concentration is greater, also, it can be seen higher densities for the ceramic obtained from calcined powders to 900 °C. The densities are greater than 98%, which is especially suitable for electronic industry application, however, these powders presented a major quantity of secondary phases [16].…”
Section: Resultsmentioning
confidence: 99%
“…The above macroscopic analysis of explaining the high EO effect is reasonable but still not comprehensive and profound. Among the references we have found so far, there is some literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]28,29] that studies ferroelectric domains of the PMN-PT ceramics, but lacks very clear domain morphology characterization. We obtained the domain morphology and studied the domain reversal (polarization behavior) from microscopic perspective to further demonstrate instability of the intermediate ferroelectric state.…”
Section: Domain Structure and Polarization Reversalmentioning
confidence: 99%
“…Utilizing the high EO effect of PMN-PT to design optical devices with tuning capability such as TOF is very valuable; however, application studies of the PMN-PT ceramics are rarely reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. To realize the application of the PMN-PT transparent ceramics in EO tunable filters, we first tested TFPF based on 2/75/25 ceramic sheet.…”
Section: Application In Tunable Filtermentioning
confidence: 99%
See 1 more Smart Citation